Comparison between paricalcitol versus cinacalcet therapy in the management of secondary hyperparathyroidism among prevalent hemodialysis patients - Maha A. Behairy; Osama Mahmoud; Ayman Rabie Ibrahim; Aber H. Baki (Society of Diabetic Nephropathy Prevention, 2022)
Introduction: Secondary hyperparathyroidism (SHPT) is one of the components of chronic kidney disease-mineral bone disorder (CKD-MBD) with significant contribution to the morbidity and mortality among prevalent hemodialysis (HD) patients. Objectives: This multi-centric experience study aims to compare the effectiveness of intravenous (IV) paricalcitol versus oral cinacalcet and oral cinacalcet plus oral alfacalcidol as treatment regimens of SHPT among chronic HD patients. Patients and Methods: This is a retrospective observational cohort study, in which 130 prevalent HD patients with SHPT was recruited from three main HD centres of Aljouf region in Saudi Arabia. Patients were divided into three groups; group I (50) HD patients were treated by IV paricalcitol, group II (50) HD patients who received oral cinacalcet plus oral alfacalcidol, group III (30) HD patients were on oral cinacalcet. Serum intact parathyroid hormone (iPTH), calcium (Ca), phosphorus (Po4) and alkaline phosphatase (ALP) tests were assessed at 0, 3, 6, and 9 months. Results: A total of 130 (61 (47%) females, (53%) 69 males) HD patients with mean age 56.30 ± 19.1 years, and with mean HD duration of 4.86±4.15 years were enrolled in the study. The mean of iPTH is significantly reduced in all studied groups (P<0.001). Mean Δchanges in iPTH concentration in groups I, II, III were -242.11±148.75, -225.54±153.91 and -254.83±275.17 respectively; P>0.05) with statistical non-significant differences. Increase of Ca×Po4 with paricalcitol group as mean ΔChange in (Ca×PO4) was in the groups I, II, III (15.39±9.46, 1.97±11.74, -2.89±9.37) respectively (P<0.001). Our study showed a significant increase in serum phosphorus from the baseline in patients of group II. Conclusion: IV paricalcitol based regimen assumed to be equally effective in suppressing SHPT in HD patients when compared to the combination of oral cinacalcet with oral alfacalcidol or treatment with oral cinacalcet alone.